Ideology in Political Speeches of World Leaders: A Rhetorical and Discourse Analysis - Azmi, Sefiani Dwi (Journal of Linguistica, 2025)
This study explores the ideological dimensions embedded in the political speeches of world leaders through the combined lenses of classical rhetoric and critical discourse analysis (CDA). By examining selected speeches from figures such as Barack Obama, Soekarno, Nelson Mandela, and Martin Luther King Jr., this research identifies how rhetorical strategies particularly ethos, pathos, and logos are employed to construct authority, mobilize public emotion, and rationalize political agendas. The analysis further reveals that language is not a neutral vehicle of communication, but a powerful instrument for shaping social reality, reinforcing dominant ideologies, and legitimizing power relations. Using CDA frameworks by Fairclough and van Dijk, the study uncovers patterns such as binary oppositions, metaphorical framing, and strategic use of pronouns to create in-group and out-group identities. These findings confirm that political speeches function as both reflections of their historical and sociopolitical contexts and as tools of ideological reproduction. The research underscores the need for critical literacy in decoding political language in an era of global media influence.